Pakistan-Kyrgyzstan Political Relations: An Appraisal - Aasia Khatoon; Skhawat; Tatheer Zahra Shirazi (ASIAN Journal of International Peace & Security (AJIPS), 2023)
Pakistan and Kyrgyzstan share common culture, believes and past and are tied in diplomatic, trade, military, security, strategic and cultural relations. In 1992, both states established diplomatic relations. Since then both states strengthened their ties and deepened cooperation in several sectors, i.e. energy, security, and trade etc. Kyrgyzstan’s soldiers get military training and education from Pakistan that enhances its security and defense capability. The major recent development in both countries’ bilateral relations is CPEC through which both are now strategically important for other regions. CPEC and Gwadar seaport connect the Central Asian states with water-resources of Arabian sea. The descriptive and analytical approach has been used to conduct this research. The theory of neoliberalism has been applied to explore and analyze both immensely growing relations and its implications on surrounding regions. The paper explores and analyzes political and military relations of both countries to find out its implications on regional peace, integration, growth, and development.